Determinants of Carbon Emission Disclosure: Does Environmental Sensitivity Strengthen The Relationship? - Amanda, Okky Wahyu; Harnovinsah, Harnovinsah; Amyulianthy, Rafrini (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This study aims to examine the influence of Corporate Environmental Performance (CEP) and Green Intellectual Capital (GIC) on Carbon Emission Disclosure (CED), with Environmentally Sensitive Industry (ESI) as a moderating variable. The research addresses corporate transparency in environmental accountability. Background Problems: Although carbon disclosure is increasingly expected by stakeholders, many firms remain inconsistent in reporting emissions. Previous studies provide mixed results on how environmental performance and intellectual capital affect disclosure, particularly in industries with significant environmental impact. Novelty: This research integrates legitimacy theory and the Triple Bottom Line framework to analyze the interaction between CEP, GIC, and ESI in relation to CED. The study’s novelty lies in testing ESI as a moderating variable and using updated data from Indonesian firms listed in the KEHATI Index. Research Methods: The study applies a quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with WarpPLS 7.0. A total of 41 companies listed in the KEHATI Index from 2020 to 2022 were selected through purposive sampling. Finding/Results: The results show that CEP and GIC positively influence CED. ESI also has a significant positive effect and strengthens the relationship between both independent variables and carbon disclosure. Conclusion: Companies with strong environmental performance and intellectual capital tend to disclose emissions more transparently. The presence of ESI enhances these relationships, suggesting that external pressure from environmentally sensitive sectors plays a critical role in driving corporate climate accountability.